2020
DOI: 10.1007/s00134-020-06192-2
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical features, ventilatory management, and outcome of ARDS caused by COVID-19 are similar to other causes of ARDS

Abstract: The main characteristics of mechanically ventilated ARDS patients affected with COVID-19, and the adherence to lung-protective ventilation strategies are not well known. We describe characteristics and outcomes of confirmed ARDS in COVID-19 patients managed with invasive mechanical ventilation (MV). Methods: This is a multicenter, prospective, observational study in consecutive, mechanically ventilated patients with ARDS (as defined by the Berlin criteria) affected with with COVID-19 (confirmed SARS-CoV-2 infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

53
323
8
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 344 publications
(402 citation statements)
references
References 32 publications
53
323
8
18
Order By: Relevance
“…Published studies on the management of ARF in COVID-19 patients have shown that the vast majority need invasive MV with prolonged times on the ventilator [19,20]. Alternatives to invasive respiratory support such as HFNO, a simple technique with few side effects, have been widely used during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies on the management of ARF in COVID-19 patients have shown that the vast majority need invasive MV with prolonged times on the ventilator [19,20]. Alternatives to invasive respiratory support such as HFNO, a simple technique with few side effects, have been widely used during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies on the management of ARF in COVID-19 patients have shown that the vast majority need invasive MV with prolonged times on the ventilator. 19,20 Alternatives to invasive respiratory support such as HFNO, a simple technique with few side effects, have been widely used during the pandemic to manage severe hypoxemia, despite initial concerns about the possibility of increased risk of virus transmission. Other adjunctive techniques, such as awake-PP, have been widely used in combination with oxygen therapy, NIV or HFNO to correct hypoxemia and avoid the need for invasive MV.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported [2,3] that severe hypoxemia with relatively well-preserved respiratory system compliance (Crs) measured under standard conditions is characteristic of COVID-19-ARDS, and it differs from ARDS of other causes (typical ARDS), while others did not recognize consistent differences [4][5][6][7]. However, the increased frequency of higher Crs in COVID-19-ARDS was noted by some of the same authors [4,5], and a significantly higher Crs associated with severe hypoxemia was recently documented [8]. The heterogeneous nature of ARDS allows that-at the population level-there may be wide overlap between COVID-19-ARDS and typical ARDS, and these observations continue to drive a debate [6,9].…”
Section: Introductionmentioning
confidence: 99%